Targeting the HIV Epidemic in South Africa: The Need for Testing and Linkage to Care in Emergency Departments. (October 2019) - Hansoti, Bhakti; Mwinnyaa, George; Hahn, Elizabeth; Rao, Aditi; Black, John; Chen, Victoria; Clark, Kathryn; Clarke, William; Eisenberg, Anna L.; Fernandez, Reinaldo; Iruedo, Joshua; Laeyendecker, Oliver; et al.
Abstract: Background: The Eastern Cape province of South Africa has one of the highest burdens of HIV in the world. Emergency Departments (EDs) can serve as optimal clinical sites for the identification of new HIV infections and entry into care. We sought to determine the current burden of HIV disease among ED patients in the Eastern Cape. Methods: We conducted a prospective cross-sectional observational study in the EDs of three Hospitals in the Eastern Cape province of South Africa from June 2017 to July 2018. All adult, non-critical patients presenting to the ED were systematically approached and offered a Point-Of-Care (POC) HIV test in accordance with South African guidelines. All HIV-positive individuals had their blood tested for the presence of antiretroviral therapy (ART) and the presence of viral suppression (≤ 1000 copies/ml). HIV incidence was estimated using a multi-assay algorithm, validated for a subtype C epidemic. Findings: Of the 2901 patients for whom HIV status was determined (either known HIV-positive or underwent POC HIV testing), 811 (28.0%) were HIV positive, of which 234 (28.9%) were newly diagnosed. HIV prevalence was higher in Mthatha [34% (388/1134) at Mthatha Regional Hospital and 28% (142/512) at Nelson Mandela Academic Hospital], compared to Port Elizabeth [22% (281/1255) at Livingstone Hospital]. HIV incidence was estimated at 4.5/100 person-years (95% CI: 2.4, 6.50) for women and 1.5 (CI 0.5, 2.5) for men. Of all HIV positive individuals tested for ART (585), 54% (316/585) tested positive for the presence of ARTs, and for all HIV positive participants with viral load data (609), 49% (299/609) were found to be virally suppressed. Interpretation: Our study not only observed a high prevalence and incidence of HIV among ED patients but also highlights significant attrition along the HIV care cascade for HIV positive individuals. Furthermore, despite developing an optimal testing environment, we were only able to enrol a small sub-set of the ED population. Given the high HIV prevalence and high attrition in the ED population, HIV services in the ED should also develop strategies that can accommodate large testing volumes and ART initiation.